1994
DOI: 10.1101/gad.8.11.1344
|View full text |Cite
|
Sign up to set email alerts
|

Functional domains within FEN-1 and RAD2 define a family of structure-specific endonucleases: implications for nucleotide excision repair.

Abstract: Structure-specific nucleases catalyze critical reactions in DNA replication, recombination, and repair. Recently, a structure-specific endonuclease, FEN-l, has been purified and shown to cleave DNA flap structures. Here, we describe the cloning of the murine FEN-1 gene. The nucleotide sequence of FEN-I is highly homologous to the 8accharomyces cerevisiae genes YKL510 and RAD2. We show that YKLS10 and a truncated RAD2 protein are also structure-specific endonucleases. The substrate specificity of the truncated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
234
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(242 citation statements)
references
References 33 publications
7
234
1
Order By: Relevance
“…rhp51 (21,29,46) is the S. pombe homolog of S. cerevisiae RAD51 which is thought to be involved in homologous pairing during recombination (52). Mammalian homologs of S. pombe rad2, and by implication rad2 itself, encode a structure-specific nuclease involved in DNA replication and/or repair (16,31,38;see Discussion). The responses to UV of the double mutants fell into two clearly different categories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…rhp51 (21,29,46) is the S. pombe homolog of S. cerevisiae RAD51 which is thought to be involved in homologous pairing during recombination (52). Mammalian homologs of S. pombe rad2, and by implication rad2 itself, encode a structure-specific nuclease involved in DNA replication and/or repair (16,31,38;see Discussion). The responses to UV of the double mutants fell into two clearly different categories.…”
Section: Resultsmentioning
confidence: 99%
“…This is a likely candidate for initiating the process. The mammalian highly conserved homolog of rad2 (16, 31) encodes a structurespecific endonuclease, called FEN-1, whose preferred substrate is a ''flap'' structure (15,16). This protein is also identical to the enzyme DNase IV (38), first isolated by Lindahl (25).…”
Section: Discussionmentioning
confidence: 99%
“…Additional genetic analysis of R THl (RAD27) has indicated that RTHl (RAD27) plays a role in repair of other types of DNA damage, that RTHl (RAD27) is a member of the RAD6 epistasis group that functions in DNA damage tolerance, and that rthl (rad27) mutants also have a cell cycle defect (Reagan et al 1995;Vallen and Cross 1995). Studies of the S. cerevisiae (called RTH1, RAD27, YKL510) and human (called FEN-1, MF-1, exonuclease IV) protein have suggested that RTHl functions in the processing of 5' ends of Okazaki fragments and processing branched DNA structures formed by different DNA repair pathways (Ishimi et al 1988;Harrington and Lieber 1994;Hiraoka et al 1995;Sommers et al 1995). There are several possible interpretations of the data on RTHl with regard to a possible role in mismatch repair.…”
Section: Other Components Required For Mismatch Repairmentioning
confidence: 99%
“…13,14 Biochemical properties of the XPG protein Analysis of the primary sequence of XPG quickly revealed that it harbors two nuclease domains placing it in the Fen1 family of structure-specific endonucleases. 9,15 Consistent with this observation XPG was shown to be a structure specific endonuclease that cleaves substrates with the polarity that would be required for the incision 3' to the lesion in NER. 15,16 XPG cleaves a variety of substrates that contain a ss/dsDNA junction, including splayed arm and bubble substrates, which contain a 5' single-stranded overhang.…”
Section: Discovery and Cloning Of Xpgmentioning
confidence: 53%
“…9,15 Consistent with this observation XPG was shown to be a structure specific endonuclease that cleaves substrates with the polarity that would be required for the incision 3' to the lesion in NER. 15,16 XPG cleaves a variety of substrates that contain a ss/dsDNA junction, including splayed arm and bubble substrates, which contain a 5' single-stranded overhang. 17,18 At the primary sequence level, XPG shares two conserved regions, the N and I regions, with other nucleases (Figure 1).…”
Section: Discovery and Cloning Of Xpgmentioning
confidence: 53%